A_inf IS INFINITE DIMENSIONAL. (11th November 2021) - Lang, Jaclyn; Ludwig, Judith
Abstract: Given a perfect valuation ring R of characteristic p that is complete with respect to a rank-1 nondiscrete valuation, we show that the ring A_ of Witt vectors of R has infinite Krull dimension.